2019
DOI: 10.18203/2320-6012.ijrms20193655
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profile and antimicrobial susceptibility patterns of otitis media among children in Qatar

Abstract: Background: Otitis Media (OM) common diseases affecting children below 5 years of age with a harmful effect on their hearing and health status. Data about the bacterial profile and current antimicrobial resistance status of Otitis Media in the region is scarce. Objective of this study determine the causative organisms of Otitis Media and antimicrobial  susceptibility patterns among children in a Primary Health Care Corporation (PPHC) centers, Qatar.Methods: A cross-sectional study was conducted in PPHC from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…This is in agreement with earlier study conducted by Waheeb; et al, reported that S. pneumoniae was the predominant agent [45]. In contrast other studies show Staphylococcus aureus [46], Pseudomonas aeruginosa [47], and Haemophilus influenzae [48]. Variation in the frequency rates of these pathogens possibly related to the different laboratory procedures used to identify bacteria, aerobic or anaerobic conditions, season, age group, vaccination status against different pathogenic bacteria and different health care programs in various geographical locations.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with earlier study conducted by Waheeb; et al, reported that S. pneumoniae was the predominant agent [45]. In contrast other studies show Staphylococcus aureus [46], Pseudomonas aeruginosa [47], and Haemophilus influenzae [48]. Variation in the frequency rates of these pathogens possibly related to the different laboratory procedures used to identify bacteria, aerobic or anaerobic conditions, season, age group, vaccination status against different pathogenic bacteria and different health care programs in various geographical locations.…”
Section: Discussionsupporting
confidence: 93%
“…Chronic suppurative otitis media (CSOM) is a chronic inflammation of the middle ear and the mastoid cavity with perforated tympanic membrane, resulting in ear discharges persisting for at least 14 days ( 1 , 2 ). If not properly treated, the disease might have long-term effects on language development, early communication, educational process, physiological and cognitive development, and auditory processing ( 3 ). By one year of age, at least 60% of children have experienced an episode, and 17% have suffered at least 3 episodes of acute otitis media (AOM) ( 4 ) which may progress to CSOM.…”
Section: Introductionmentioning
confidence: 99%